ChemInform Abstract: Consecutive Reactions Between Methyl 3‐Dehydroshikimiate, Amines and 1, 2‐Dichloroalkanes under Microwave Conditions: A Practical, One‐Pot Construction of N‐Substituted Dihydrobenzoxazines. Issue 42 (14th October 2014) - Zhang, Ensheng; Xu, Tianlong; Wang, Dejian; Huang, Tongkun; Yuan, Mu; Li, Jun; Zou, Yong
Abstract Microwave promoted reaction of 3‐dehydroshikimate (I) with primary amines or the hydrazone (IV) and 1, 2‐dichloroethane as bisnucleophile permits the efficient synthesis of 1, 4‐benzoxazines.